Assessment of algorithms to identify patients with thrombophilia following venous thromboembolism. (January 2016) - Delate, Thomas; Hsiao, Wendy; Kim, Benjamin; Witt, Daniel M.; Meyer, Melissa R.; Go, Alan S.; Fang, Margaret C.
Abstract: Introduction: Routine testing for thrombophilia following venous thromboembolism (VTE) is controversial. The use of large datasets to study the clinical impact of thrombophilia testing on patterns of care and patient outcomes may enable more efficient analysis of this practice in a wide range of settings. We set out to examine how accurately algorithms using International Classification of Diseases 9th Revision (ICD-9) codes and/or pharmacy data reflect laboratory-confirmed thrombophilia diagnoses. Materials and methods: A random sample of adult Kaiser Permanente Colorado patients diagnosed with unprovoked VTE between 1/2004 and 12/2010 underwent medical record abstraction of thrombophilia test results. Algorithms using "ICD-9" (positive if a thrombophilia ICD-9 code was present), "Extended anticoagulation (AC)" (positive if AC therapy duration was > 6 months), and "ICD-9 & Extended AC" (positive for both) criteria to identify possible thrombophilia cases were tested. Using positive thrombophilia laboratory results as the gold standard, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value of each algorithm were calculated, along with 95% confidence intervals (CIs). Results: In our cohort of 636 patients, sensitivities were low (< 50%) for each algorithm. "ICD-9" yielded the highest PPV (41.5%, 95% CI 26.3–57.9%) and a high specificity (95.9%, 95% CI 94.0–97.4%). "Extended AC" had the highest sensitivity but lowest specificity, and "ICD-9 & Extended AC" had the highest specificity but lowest sensitivity. Conclusions: ICD-9 codes for thrombophilia are highly specific for laboratory-confirmed cases, but all algorithms had low sensitivities. Further development of methods to identify thrombophilia patients in large datasets is warranted. Highlights: Thrombophilia ICD-9 codes are highly specific for thrombophilia results. Extended anticoagulation does not correlate with thrombophilia laboratory results. ICD-9 codes + anticoagulation duration does not improve thrombophilia detection.